Stimuli-responsive metal–organic supercontainers as synthetic proton receptors. Issue 30 (17th July 2018) - Sun, Cheng-Zhe; Cheng, Li-Ji; Qiao, Yupu; Zhang, Li-Yi; Chen, Zhong-Ning; Dai, Feng-Rong; Lin, Wei; Wang, Zhenqiang
Abstract : Functional supercontainers exhibit intriguing H + -dependent fluorescent switching behavior, opening exiting new opportunities for proton modulation in both chemistry and biology. Abstract : We demonstrate a proof-of-concept design of a new platform for proton recognition and modulation. The new proton receptors are derived from a unique class of synthetic supercontainers that exhibit exceptional proton binding capacity (over 50 equiv.) and intriguing proton-dependent fluorescent switching behavior. Experimental and computational studies suggest that the proton-responsive event involves a two-step mechanism pertaining to proton binding by both amino and pyrenyl moieties of the supercontainer constructs. The high proton binding capacity of the supercontainers can be further modulated via small-molecule "regulators" that compete for the proton-binding sites, opening exiting new opportunities for proton manipulation in both chemistry and biology.